A Case Report: Ayurvedic Management of DMD w.s.r to Mamsagata-Vata - Mridula; Sahoo, Preetimayee; Mahanta, Nihar Ranjan (International Research Journal of Ayurveda & Yoga, 2024)
Duchenne Muscular Dystrophy (DMD) describes generalized progressive muscular weakness due to the wasting of muscle fibres. It is the most widespread lethal genetic disease of humans. The progression is affected by known immunological and mechanical factors, and possibly other unknown mechanisms. Sufferers become increasingly disabled as the disease progresses & caring for the affected child in resource poor settings face a lot challenges. DMD have a lack of effective treatment. Glucocorticoids are the standard of care in DMD until now and its long term use are not devoid from crucial complications mainly in long term use like poor bone health, obesity, neurologic impairments, cardiac & respiratory problems. Hence, an alternative therapy is needed. Thus, case study was conducted considering DMD as Mamsagata-vata and Ayurvedic management Niruha Basti having Panchatikta ghrita, Mashapinda-sveda was planned accordingly. During & after treatment, a positive outcome in mobility & self-care was noted